Unfolding the hidden structure of the Hungarian multi-layer firm network - Andras Borsos; Martin Stancsics (Magyar Nemzeti Bank, 2020)
In this paper we offer an explorative, mainly descriptive analysis about the multi-layered network of Hungarian firms. To conduct this study, we obtained access to firm-level supplier information, on which we could superimpose also the ownership background of all Hungarian companies. Our primary focus was to explore the topological origins of shock propagation phenomena among firms. As both the supplier and the ownership layers are considered to be among the most significant shock-transmitting mediums, our data is ideal to gain insight into previously unobserved structural drivers of spreading processes. We found (i) several topological traits on micro-, meso-, and macro-scale as well, which can be responsible for facilitating contagious processes via supplier links; (ii) we could also identify separated blocks of the economy (representing different production chains) within which shocks can more freely spread in the system; (iii) furthermore, we could assess the significance of economic entities regarding the extent they can influence the economy via their ownership relations.
Keywords: C63; C67; C81; G32; L23; 330; ownership network; production network; supply chain; spillover; shock propagation; contagion